Effect of Pain and Mild Cognitive Impairment on Mobility. Issue 1 (19th January 2016) - Schepker, Caroline A.; Leveille, Suzanne G.; Pedersen, Mette M.; Ward, Rachel E.; Kurlinski, Laura A.; Grande, Laura; Kiely, Dan K.; Bean, Jonathan F.
Abstract : Objectives: To examine the effect of pain and mild cognitive impairment (MCI)—together and separately—on performance‐based and self‐reported mobility outcomes in older adults in primary care with mild to moderate self‐reported mobility limitations. Design: Cross‐sectional analysis. Setting: Academic community outpatient clinic. Participants: Individuals aged 65 and older in primary care enrolled in the Boston Rehabilitative Impairment Study in the Elderly who were at risk of mobility decline (N = 430). Measurements: Participants with an average score greater than three on the Brief Pain Inventory (BPI) were defined as having pain. MCI was defined using age‐adjusted scores on a neuropsychological battery. Multivariable linear regression models assessed associations between pain and MCI, together and separately, and mobility performance (habitual gait speed, Short Physical Performance Battery), and self‐reports of function and disability in various day‐to‐day activities (Late Life Function and Disability Instrument). Results: The prevalence of pain was 34% and of MCI was 42%; 17% had pain only, 25% had MCI only, 17% had pain and MCI, and 41% had neither. Participants with pain and MCI performed significantly worse than all others on all mobility outcomes ( P  < .001). Participants with MCI only or pain only also performed significantly worse on all mobility outcomes than those with neither ( P  < .001). Conclusion: Mild to moderate pain and MCI were independently associated with poor mobility, and the presence of both comorbidities was associated with the poorest status. Primary care practitioners who encounter older adults in need of mobility rehabilitation should consider screening them for pain and MCI to better inform subsequent therapeutic interventions.